Study on the Factors Affecting Housing Prices in Chengdu: Empirical analysis based on data from 2002-2022 - Tao, Zhongyu (International Journal of Global Economics and Management, 2024)
Based on the background of the sluggish real estate market in recent years, this paper organizes the relevant data on the average selling price of commercial housing in Chengdu from 2002 to 2022 and studies the factors affecting housing prices. It also collects data such as per capita GDP, housing completion area, and real estate development investment in Chengdu from 2002 to 2022, and constructs the STIRPAT model for multiple linear regression. After a series of model tests and empirical analysis, it is concluded that both per capita GDP and real estate development investment have a positive effect on Chengdu housing prices, while the housing completion area is negatively correlated with Chengdu housing prices. Based on the research results, this paper summarizes the conclusions and puts forward suggestions for the Chengdu Municipal Government and real estate developers.